If I could write this in fire : an anthology of literature from the Caribbean - Smorkaloff, Pamela Mar ia, 1956- (New York : New Press, 1994)
"Global awareness of the Caribbean has come a long way from Columbus' colossal geographic error, but few readers are familiar with the diverse legacy of literature that has come out of this besieged region."--BOOK JACKET. "In an unprecedented collection, If I Could Write This in Fire brings together fiction from the French-, Spanish-, and English-speaking Caribbean, much of it translated here for the first time, and illustrates the bridges built from one island society to another as all struggled to respond to the shared experience of conquest."--BOOK JACKET. "The fifteen selections deal with basic, underlying themes of the region's literature: the plantation, maroon society, colonial education, rural and urban life, women's changing roles in the modern Caribbean, exile, and the diaspora. Works include Jamaican author James Carnegie's powerful novella Wages Paid about a day in the life of a slave plantation, a selection by noted Guadeloupan novelist Simone Schwarz-Bart, Puerto Rican short stories from Ana Lydia Vega, and fiction from the Dominican Republic, Cuba, St. Kitts, and Barbados. Together they offer the first picture of a Caribbean voice and aesthetic, and an extensive bibliography of further reading invites students, scholars, and others to explore beyond this initial collection."--BOOK JACKET. "From Columbus' diaries on, the Caribbean has been the scene onto which a steady stream of myths has been imposed. If I Could Write This in Fire offers the first collection of authentic Caribbean voices - a small set of gems that will introduce readers to a rich and lyric tradition."--Jacket.
Literary selections. The plantation and maroon society. Wages paid / James Carnegie -- From : The autobiography of a runaway slave / Esteban Montejo, edited by Miguel Barnet -- Rural peasantry. From : Between two worlds / Simone Schwarz-Bart -- From : When they loved the communal lands / Pedro Mir -- Decolonization and the colonial education. From : Growing up stupid under the union jack / Austin Clarke -- Journey back to the source / Alejo Carpentier -- Isolation/inter-Caribbean relations. The day it all happened ; Port-au-Prince, below / Ana Lydia Vega -- Modern life : alienation/liberation. From : A state of independence / Caryl Phillips -- Monologue with rain ; Common stories / Chely Lima -- Passing / Michelle Cliff -- Theoretical essays. Identity, historiography, and the Caribbean voice. From : The black Jacobins / C.L.R. James -- Caliban : notes toward a discussion of culture in our America / Roberto Fern andez Retamar -- If I could write this in fire, I would write this in fire / Michelle Cliff.
In English; many selections have been translated from the French and Spanish.
Includes bibliographical references (pages 371-373).
NLJCols20082021
Keywords: Caribbean literature; Caribbean literature; Litt erature antillaise de langue anglaise -- Anthologies; Litt erature antillaise -- Anthologie; Dust jackets -- Specimens -- Jamaica -- 20th century